PENGARUH LIKUIDITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR PERTAMBANGAN BATU BARA DI BURSA EFEK INDONESIA - Nurhidaya, A.; Sahade, Sahade; Idris, Hariany (Jurnal Sains Riset, 2024)
This study aims to analyze the effect of liquidity on stock prices in coal mining companies listed on the Indonesia Stock Exchange (IDX). The variables in this study are liquidity as an independent variable, and stock price as a dependent variable. The population in this study is coal mining companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022 as many as 19 companies. Sampling is carried out using purposive sampling techniques, which are sampling techniques with certain considerations and criteria with a sample of 18 companies. The data collection technique used is documentation. Data analysis techniques use normality tests, simple linear regression analysis, coefficients of determination and partial tests (t tests). Based on the results of research that liquidity has a significant effect on stock prices in coal mining companies listed on the Indonesia Stock Exchange (IDX). Based on the results of the study that: (1) The results of a simple linear regression analysis obtained the equation Y' = 6.951 + 1.263X. This means that every increase in one unit of liquidity variable, the stock price will increase by 1,263. (2) The result of the coefficient of determination is 0.260 or 26 percent. This means that liquidity is able to explain 26 percent of the stock price, while the remaining 74 percent is influenced by other factors. (3) The results of the t-test obtained sig value results 0.000 0.05 which means that liquidity variables have a positive and significant effect on stock prices in coal mining companies listed on the Indonesia Stock Exchange (IDX), so the hypothesis is accepted. Keywords: Liquidity, Share Price